2005
DOI: 10.1002/fld.878
|View full text |Cite
|
Sign up to set email alerts
|

Reduced basis simulations as a tool for generating turbulent inlet‐data for two opposing jets

Abstract: SUMMARYReduced basis simulations are used in order to generate turbulent inlet boundary conditions for a direct numerical simulation of two opposing wall jets. The two entering jets are fully turbulent channel ows of Reynolds number 180, based on friction velocity and half channel height. The in ow turbulence is generated by solving dynamical equations for the large scales only, while less energetic small scales are added randomly. The proper orthogonal decomposition method is used to identify the large scale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
(19 reference statements)
1
2
0
Order By: Relevance
“…Such effect becomes highly pronounced as more opposing jets (shown later) are involved with a smaller separation distance, since the resulting pressure of impingement (dominating across a larger spherical zone) will approach the ports further. This is supported by the computations of Johansson and Andersson 6 who found that (for two opposing jets of 2 cm diameter and 20 cm separation distance) a separation bubble of 8 cm diameter develops in the stagnation region with a peak pressure of nearly 70 Pa. The subsequent influence of the stagnation pressure on the flow development near the ports in their work is currently reproduced in Figure 5(a) when the separation distance is decreased to 9 cm (with X = 45 mm from the port to the impact point where the pressure reaches a peak of 154 Pa).…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…Such effect becomes highly pronounced as more opposing jets (shown later) are involved with a smaller separation distance, since the resulting pressure of impingement (dominating across a larger spherical zone) will approach the ports further. This is supported by the computations of Johansson and Andersson 6 who found that (for two opposing jets of 2 cm diameter and 20 cm separation distance) a separation bubble of 8 cm diameter develops in the stagnation region with a peak pressure of nearly 70 Pa. The subsequent influence of the stagnation pressure on the flow development near the ports in their work is currently reproduced in Figure 5(a) when the separation distance is decreased to 9 cm (with X = 45 mm from the port to the impact point where the pressure reaches a peak of 154 Pa).…”
Section: Resultssupporting
confidence: 57%
“…It is thus highlighted that multiple opposing jets are an effective mechanism to merge their respective powerful shearing zones in the vicinity of their ports. Johansson and Andersson 6 stated that the mean rate of the normal strain is important in such stagnating flows due to the highly adverse pressure gradient, whereby a considerable streamline curvature exists. They found that the consequent increase in the maximum turbulent energy from the jet inlet to the stagnation region is about 500%.…”
Section: Introductionmentioning
confidence: 99%
“…2) as respectively resulting from the normal strain and the radial shearing. 31 On the other hand, a single zone (No. 4) develops on each shearing side of the cross-flow jet and gets additional strain effects from the vortical flow zone (No.…”
Section: Nox Emissions From the Multiple Pairs Of Opposing Jets' Burnermentioning
confidence: 99%